Analisis Standar Operasional Prosedur Dalam Pengamanan Pertandingan Sepak Bola: Studi Kasus Stadion Kanjuruhan - Muhammad Maureno Davit Geovany; Haniyah Haniyah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Supporters are people who provide active support. These supporters are different from ordinary football spectators who only see the football match because supporters are football spectators who support a certain team, and are ready to give up all their energy in motivating their favorite club. These football fans are very active and have excessive fanaticism for the team they support. It is this fanaticism that usually causes chaos and riots at every football match in Indonesia. Because riots and riots in soccer matches often occur, the police, in this case the police, tighten security at every soccer match. However, the tight security often leads to repressive actions that lead to violence against supporters by the police in securing football matches. The violence perpetrated by the security forces against the fans clearly violated the provisions of the applicable law. And this is a violation of the law for which there must be criminal accountability for the perpetrators of the violence so that there is no more violence experienced by fans in football matches.